Dual-functional probe for sensitive detection of MCF-7 cells and mendelian randomization analysis of MUC1 association with multiple cancers - Zhuzheng Wu; Qingquan Chen; Zhifeng Lin; Yating Chen; Xiaohao Gan; Ye He (Scientific Reports)
Abstract The present study successfully developed a method based on a dual-functional probe for detecting breast cancer cells MCF-7 by recognizing the MUC1 protein on the cell surface. This method integrated inductively coupled plasma mass spectrometry (ICP-MS) and fluorescence imaging technology, enhancing the sensitivity, specificity, and accuracy of breast cancer cell detection. Additionally, through two-sample Mendelian randomization (MR) analysis, we verified a potential correlation between breast cancer and MUC1 (PIVW<0.05), while also proving no potential correlation between liver cancer and MUC1 (PIVW>0.05). Furthermore, this study explored the relationship between other cancers and MUC1, indicating a potential correlation between ovarian cancer and colorectal cancer with MUC1 (PIVW<0.05). In summary, this study provides new strategies for the early diagnosis and treatment of breast cancer and offers new insights into the potential of MUC1 as a biomarker for the detection of other cancers.